COMPUTER SCIENCE PERFORMANCE - RESOURCES, PARADIGMS, IMPACT - CERCHEZ, Emanuela (Acta et Commentationes, Sciences of Education, 2019)
The article identifies the ways in which the Olympiads and competitions influence the quality of computer science education. Two terms are defined: Olympic and performance. The differences and analogies between "competition" and "class" problems, "competition" evaluation versus "class" evaluation are indicated. Also, the auxiliary tools of the training program for the programming competitions are analyzed, such as: online performance training platforms (.camp, infoarena etc.). Two paradigms of performance training are analyzed: the segregated model, the integrated model. The article also deals with software creativity contests in which students present a complex application, developed over time. Such contests do not exclude algorithms, because any program involves the implementation of an algorithm.